The Impact of Terrorism on Financial Markets - Croitoru, Oana (IMF Working Papers; Working Paper ;, 2005)
The terrorist attacks that have occurred in the past few years around the world have raised international awareness of the danger of terrorism and its complex repercussions on the financial markets. This paper explores the ways in which financial markets reacted to the attacks and the authorities' responses. Well-functioning financial markets, bolstered by the prompt and effective reaction of the relevant authorities, were generally efficient in absorbing shocks stemming from terrorist attacks. The paper discusses market and regulatory responses to the terrorist attacks and the elements that should be strengthened so as to further enhance the resilience of financial markets to terrorism.